Increase in Tumor Control and Normal Tissue Complication Probabilities in Advanced Head-and-Neck Cancer for Dose-Escalated Intensity-Modulated Photon and Proton Therapy - Jakobi, Annika; Lühr, Armin; Stützer, Kristin; Bandurska-Luque, Anna; Löck, Steffen; Krause, Mechthild; Baumann, Michael; Perrin, Rosalind; Richter, Christian (Frontiers in Oncology, 2015)
Introduction: Presently used radio-chemotherapy regimens result in moderate local control rates for patients with advanced head and neck squamous cell carcinoma (HNSCC). Dose escalation (DE) may be an option to improve patient outcome, but may also increase the risk of toxicities in healthy tissue. The presented treatment planning study evaluated the feasibility of two DE levels for advanced HNSCC patients, planned with either intensity-modulated photon therapy (IMXT) or proton therapy (IMPT). Materials and Methods: For 45 HNSCC patients, IMXT and IMPT treatment plans were created including DE via a simultaneous integrated boost (SIB) in the high-risk volume, while maintaining standard fractionation with 2 Gy per fraction in the remaining target volume. Two DE levels for the SIB were compared: 2.3 Gy and 2.6 Gy. Treatment plan evaluation included assessment of tumor control probabilities (TCP) and normal tissue complication probabilities (NTCP). Results: An increase of approximately 10% in TCP was estimated between the DE levels. A pronounced high-dose rim surrounding the SIB volume was identified in IMXT treatment. Compared to IMPT, this extra dose slightly increased the TCP values and to a larger extent the NTCP values. For both modalities, the higher DE level led only to a small increase in NTCP values (mean differences < 2%) in all models, except for the risk of aspiration, which increased on average by 8% and 6% with IMXT and IMPT, respectively, but showed a considerable patient dependence. Conclusions: Both DE levels appear applicable to patients with IMXT and IMPT since all calculated NTCP values, except for one, increased only little for the higher DE level. The estimated TCP increase is of relevant magnitude. The higher DE schedule needs to be investigated carefully in the setting of a prospective clinical trial, especially regarding toxicities caused by high local doses that lack a sound dose response description, e.g., ulcers.